The Role of Artificial Intelligence in Enhancing Medication Adherence: A Mini Review - Ghozali, Muhammad Thesa (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Medication adherence is essential for optimal healthcare outcomes, particularly in managing chronic conditions like diabetes, hypertension, and cardiovascular diseases. Despite its significance, nonadherence remains a widespread issue, contributing to disease progression, hospitalizations, and increased mortality. Traditional interventions such as patient education and reminders have shown limited scalability and efficacy. This review explores the transformative potential of artificial intelligence (AI) in enhancing medication adherence, synthesizing evidence from peer-reviewed studies. AI tools, including mobile applications, wearable devices, ingestible biosensors, and platforms like AiCure, provide personalized, real-time monitoring and tailored interventions to support adherence. These technologies demonstrate significant improvements in adherence rates and patient engagement, especially for chronic and complex conditions. However, challenges such as data privacy concerns, digital literacy gaps, and integration barriers with existing healthcare systems hinder widespread adoption. Addressing these challenges through robust regulatory frameworks, enhanced accessibility, and system interoperability is critical. Future directions include leveraging advancements in reinforcement learning, explainable AI, and collaborative initiatives to ensure equitable and effective use of AI in adherence management. AI offers a promising pathway to improve adherence outcomes and healthcare efficiency, provided ethical, infrastructural, and accessibility challenges are adequately addressed.